Sweet Brine: Innovative Procedure to Convert Hard-Rinded Fruit Wastes to Bonbon Desserts (Philippine Journal of Agricultural Economics, 2019)
In 2015, the Department of Environment and Natural Resources in its October Waste Manual revealed that over 40% of the wastes in local communities are biodegradable leftovers from vegetables and fruits. The study aimed to produce a viable concoction upon which vegetable peelings and other biodegradable leftovers could be recycled and be made edible. Using the trial and error method system, the study employed three mixture solutions: vinegar and salt, wine and beer, and water and baking soda which were tested with rinds of papaya, watermelon, and lemon. The research yielded two-pronged outputs: 1) a scientifically sound solution to recycle hard-rinded fruit wastes, and 2) an innovative procedure on how to use the solution in converting fruit rinds to sweet bonbon desserts. The procedure involved peeling the rinds until the hardcore remains, immersing the core to the solution for 10 days and then drying the rinds, cooking them under low heat with caramelized sugar and serving as tarts or bonbon. The study was carried out following the main postulates of science when it comes to boiling, drying, dehydrating, preserving, powdering and processing of fruit rinds into candied versions. Chemicals used for the study were as follows: water and baking soda with the ratio of 4:2; wine and beer in equal part and vinegar and salt solution in equal parts in 50ml of water.  Upon evaluation, it was found out that the drying time significantly affected the moisture content of the dehydrated watermelon rind candies.